Examining the nature, causes, and consequences of profiles of organizational citizenship behavior. (29th December 2017) - Klotz, Anthony C.; Bolino, Mark C.; Song, Hairong; Stornelli, Jason
Summary: Research on organizational citizenship behavior (OCB) typically focuses on either one type of OCB or an aggregate of multiple types of OCB. We investigate a third conceptualization of OCB by examining how employees use conscientiousness, sportsmanship, civic virtue, courtesy, and altruism in distinct combinations. In Study 1, we identify 5 profiles of citizenship in a sample of 129 workers in a medium‐sized firm. Some employees used either high levels (prosocial citizens), above average levels (contributors), or low levels of all 5 OCBs (disengaged). Another profile of employees (specialists) displayed relatively high levels of civic virtue and altruism, and a final profile of employees (moderates) engaged in below‐average levels of all OCBs except conscientiousness. We also found that organizational concern citizenship motives related to these profiles. In Study 2, using a more generalizable sample of over 400 employees, we replicated 4 of the 5 profiles and identified a group of employees who mainly engaged in OCBs aimed at others (good coworkers). Using data collected at 3 points in time, we also found that citizenship motives (impression management, prosocial values, and organizational concern) predicted all 5 OCB profiles and that these profiles predicted job performance ratings, workplace status, and citizenship fatigue.